Studies in the life of Christ ; v. 1 - Foster, Rupert Clinton, 1888-1970 (Cincinnati Standard, 1938)
Contents : v. 1 : Early period. Includes index.
Donated by the author : inscription reads : The Library at the Emmaus Bible School, Epping, Australia. Sept 29, 1962; R.C. Foster
Keywords: Jesus Christ -- biography